Microstructural and thermoanalytical characterization of super duplex stainless steel - UNS S32760-F55. (September 2021) - Khoshnaw, Fuad; Marinescu, Cornelia; Sofronia, Ancuta; Munteanu, Cornel; Marcu, Maria; Barbulescu, Laura Eugenia; Ciobota, Cristina; Cojocaru, Elisabeta Mirela; Tanasescu, Speranta; Paraschiv, Alexandru
Abstract: Super Duplex Stainless Steel (SDSS) alloys, due to their high strength, toughness, and corrosion resistance properties, are widely used in aggressive conditions. However, once SDSS is exposed to an elevated temperature environment during welding, forging, hot working, heat treatment, casting, and aging, the undesired sigma (σ) phase can form, which reduces the corrosion resistance and toughness. In this study, the microstructural evolution of the sigma phase in SDSS type UNS S32760 F55 under heating was correlated with the thermodynamic functions of the phase transformations. Samples were isothermally aged at different temperatures in the range of 573.15–1373.15 K using two different time intervals, 30 min and 6 h, in both air and Ar gas. The results showed that the formation of the σ phase depends on the cooling rate, as 3% of the σ phase was formed in water quenched alloy. The peak of the transformation to sigma and secondary austenite phases was observed at 1023.15 K, which was strongly dependent on the aging time, rather than the aging environment. Electrochemical results revealed a good corrosion resistance for the as-received alloy in 3.5% NaCl solution. This study points out how the results obtained by calorimetry methods are used to express the microstructural evolution of an alloy into macroscopic thermodynamic parameters. The high-temperature thermodynamic data offer significant insights into the design of an alloy that can be used in harsh environments. Highlights: High-temperature thermodynamic data of super duplex alloy. The eutectoid transformation occurred within the 923.15–1123.15 K temperature range. Relation between microstructural properties and macroscopic thermodynamic properties.